The past, present and future of anticholinergic drugs - David Healy (SAGE Publishing, 2023)
In current medical practice, it is difficult to find any reports claiming that drugs that are primarily anticholinergic or those that have significant anticholinergic effects have any therapeutic benefits. These drugs fell into disrepute within the mental health field from the mid-1960s onwards, and their supposed problems extended to elsewhere in medicine after that. There is considerable evidence that this disrepute stemmed more from marketing copy rather than from hard clinical trial data. Many apparent reviews appear to repeat prior claims rather than present substantial or new evidence. This article offers a perspective rather than a systematic review as there is little evidence other than claims to review. The aim is to challenge the conventional narrative that anticholinergic effects are uniquely hazardous by pointing to the uncertain basis for claims about the harms of anticholinergic drugs, antimuscarinic drugs in particular, ending with pointers to recent research that, if realized, might underpin important possible future benefits.